Sound localization and auditory selective attention in school-aged children with ADHD - Fu, Tong; Li, Bingkun; Yin, Weizhen; Huang, Shitao; Liu, Hongyu; Song, Yan; Li, Xiaoli; Shang, Herui; Zhou, Yanling; Cheng, Daomeng; Cao, Liping; Dang, Cai-Ping (Frontiers in Neuroscience, 2022)
The aim of this study was to identify the neurophysiologic bases of auditory attention deficits in children with attention-deficit/hyperactivity disorder (ADHD), focusing on electroencephalography markers of auditory spatial selective attention (the N2 anterior contralateral component [N2ac]). EEG data were collected from 7−11-year-old children with ADHD (n = 54) and age-, sex-, and IQ-matched typically developing (TD) children (n = 61) while they performed an auditory spatial selective task. For behavior, the children with ADHD showed a shorter reaction time (RT) but a higher RT coefficient of variability (RTCV) than TD children. For ERPs, the TD group showed a significant “adult-like” N2ac component; however, the N2ac component was absent in children with ADHD. More importantly, the smaller N2ac component could predict longer RT in both groups, as well as higher severity of inattentive symptoms in children with ADHD. Our results indicated that 7−11-year-old TD children have developed an “adult-like” ability to balance auditory target selection and distractor suppression; the absence of N2ac in children with ADHD provided novel evidence supporting their impaired auditory spatial selective attention.